Tissue Handling and Specimen Preparation in Surgical Pathology: Issues Concerning the Recovery of Nucleic Acids From Formalin-Fixed, Paraffin-Embedded Tissue - Hewitt, Stephen M.; Lewis, Fraser A.; Cao, Yanxiang; Conrad, Richard C.; Cronin, Maureen; Danenberg, Kathleen D.; Goralski, Thomas J.; Langmore, John P.; Raja, Rajiv G.; Williams, P. Mickey; Palma, John F.; Warrington, Janet A. (Archives of pathology & laboratory medicine (1976), 2008)
Context.—Expression profiling by microarrays and real-time polymerase chain reaction–based assays is a powerful tool for classification and prognostication of disease; however, it remains a research tool, largely reliant on frozen tissue. Limiting the utility of expression profiling is the isolation of quality nucleic acids from formalin-fixed, paraffin-embedded tissue. The collection, handling, and processing of tissue directly impacts the biomolecules that can be recovered from it. High-quality nucleic acids can be obtained from formalin-fixed, paraffin-embedded tissue, but greater attention to all steps in the process of tissue handling and preparation is required. Objective.—To summarize the current state-of-the-art of preanalytic factors in tissue handling and processing as they impact the quality of RNA obtainable from formalin-fixed, paraffin-embedded tissue. The goals are to provide recommendations that will improve RNA quality for expression profiling from formalin-fixed, paraffin-embedded tissue and highlight areas for additional research. Tissue is an analyte and it must be handled in a standardized fashion to provide consistent results. Data Sources.—The literature was reviewed. Consultation with industry and academic leaders in the use of RNA for expression profiling was obtained to identify areas for additional research. Conclusions.—Development of RNA-based assays from formalin-fixed, paraffin-embedded tissue is feasible. Greater attention to tissue handing and processing is essential to improve the quality of biospecimens for the development of robust RNA-based assays. Standardization of procedures and vigorous testing of alternative protocols are required to ensure that these assays function as designed.